(untitled) (Journal of the College of Basic Education, 2024)
The methods followed by the local Kurdish leaderships in their opposition to direct British rule and in obtaining their national rights differed. While some of them resorted to uprisings and revolutions, or the use of force of arms, others resorted to forming associations and political parties, whether those formed in public ways or those that worked in secret ways. In the midst of those events, the Kurds formed associations and parties in the city of Sulaymaniah that played a major role in the history of the cotemporary Kurds.